Basement Membrane Zone Collagens XV and XVIII/Proteoglycans Mediate Leukocyte Influx in Renal Ischemia/Reperfusion - Zaferani, Azadeh (Public Library of Science, 2014)
Collagen type XV and XVIII are proteoglycans found in the basement membrane zones of endothelial and epithelial cells, and known for their cryptic anti-angiogenic domains named restin and endostatin, respectively. Mutations or deletions of these collagens are associated with eye, muscle and microvessel phenotypes. We now describe a novel role for these collagens, namely a supportive role in leukocyte recruitment. We subjected mice deficient in collagen XV or collagen XVIII, and their compound mutant, as well as the wild-type control mice to bilateral renal ischemia/reperfusion, and evaluated renal function, tubular injury, and neutrophil and macrophage influx at different time points after ischemia/reperfusion. Five days after ischemia/reperfusion, the collagen XV, collagen XVIII and the compound mutant mice showed diminished serum urea levels compared to wild-type mice (all p<0.05). Histology showed reduced tubular damage, and decreased inflammatory cell influx in all mutant mice, which were more pronounced in the compound mutant despite increased expression of MCP-1 and TNF-α in double mutant mice compared to wildtype mice. Both type XV and type XVIII collagen bear glycosaminoglycan side chains and an in vitro approach with recombinant collagen XVIII fragments with variable glycanation indicated a role for these side chains in leukocyte migration. Thus, basement membrane zone collagen/proteoglycan hybrids facilitate leukocyte influx and tubular damage after renal ischemia/reperfusion and might be potential intervention targets for the reduction of inflammation in this condition.